Development of theoretical principles of risk management of innovative activities of industrial enterprises in Russia in the context of digitalization - O. N. Kiseleva; G. V. Safaryan (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. At the present stage of economic development, the problem of innovative development of domestic industrial enterprises is particularly acute, which is determined by the current geopolitical situation and the need to ensure national security and sovereignty of our state. In this context, the role of innovation risk management is also increasing, the eﬀectiveness of which depends on obtaining the desired result. One of the most important factors ensuring the eﬀectiveness of risk management in the ﬁeld of innovative development is currently digitalization, which provides a wide range of opportunities for eﬀective management. However, today the emphasis is on "digital" risks in innovation, which signiﬁcantly reduces the potential of digitalization in terms of managing the negative impact of challenges and threats arising in the process of developing and implementing innovations.Goal. The article aims is the development of theoretical provisions of risk management, taking into account the requirements of modernity, expressed in universal digitalization, which will allow using its advantages.Materials and methods. The study was conducted on the basis of the use of dialectical, historical, comparative and theoretical methods, the application of which made it possible to identify existing approaches to risk management of innovative activities of industrial enterprises, to identify the speciﬁcs of views on the problems of interaction between innovative and digital development, to determine the possible direction of theoretical development of the provisions. The research materials included works by domestic and foreign authors, regulatory legal acts and expert opinions.Results and discussion. The analysis of existing provisions allowed the authors to propose a digital approach to risk management of innovative activities of industrial enterprises based on the use of digital technologies that provide a wide range of opportunities to identify and implement the necessary impact on risks.Conclusion. The proposed approach will expand the range of possible solutions for managing innovation risks, as well as increase the eﬀectiveness of management decisions, which will contribute to achieving the development goals set by the state.